Genetic analysis of single disseminated tumor cells in the lymph nodes and bone marrow of patients with head and neck squamous cell carcinoma. Issue 2 (31st October 2021) - Sproll, Karl Christoph; Schorn, Lara K.; Reising, Benedikt; Schumacher, Sarah; Lommen, Julian; Kübler, Norbert R.; Knoefel, Wolfram Trudo; Beier, Manfred; Neves, Rui P.; Behrens, Bianca; Horny, Kai; Stoecklein, Nikolas H.
Abstract : Considering the limited information on the biology and molecular characteristics of disseminated tumor cells (DTCs) in head and neck squamous cell carcinoma (HNSCC), we examined the genomic alterations in DTCs from HNSCCs and their potential clinical relevance. To analyze both the lymphatic and hematogenous routes of tumor cell dissemination, we investigated samples from lymph nodes (LNs) and bone marrow (BM) of 49 patients using immunofluorescence double staining for epithelial cells expressing cytokeratin 18 (KRT18) and/or epithelial cell adhesion molecules (EpCAM, CD326). The identified marker‐positive cells were isolated by micromanipulation followed by single‐cell whole‐genome amplification and metaphase‐based comparative genomic hybridization (mCGH) to determine genome‐wide copy number alterations. The findings were correlated with clinical parameters and follow‐up data. We detected chromosomal aberrations in KRT18‐ and EpCAM‐positive cells from both compartments; BM‐derived cells showed a significantly higher percentage of aberrant genome (PAG) per cell than cells detected in LNs. No significant association was found between DTC data and clinical follow‐up. Genomic profiling of BM‐DTCs revealed genomic alterations typical for HNSCC, suggesting hematogenous dissemination of subclones around the time of surgery. In contrast, DTC data in LNs revealed that several marker‐positive cells were not of malignant origin, indicating the presence of epithelial glandular inclusions in parts of the processed neck LN samples. Therefore, DTC detection of LNs in the neck based only on epithelial markers is not advisable and requires detection of chromosomal instability (CIN), gene mutations, or additional markers, which have yet to be identified. Nevertheless, our investigation paves the way for larger studies to focus on HNSCC BM‐DTCs with high‐resolution methods to gain deeper insights into the biology of hematogenous metastasis in this cancer. Abstract : We isolated disseminated tumor cells from lymph nodes and bone marrow of patients with head and neck squamous cell carcinoma and comprehensively characterized them genetically at the single cell level. While the cells in the lymph nodes are harder to identify, those in the bone marrow showed up as highly aberrant subclones that could possibly become the starting point for distant metastases.